Analysis of Factors Related To the Nutritional Status of Toddlers at Moanemani Community Health Center Dogiyai District - Nopelice Anou; Nur Al-faida; Gandhi Pratama (Lembaga Pengembangan Kinerja Dosen, 2025)
Toddlers are the age group that most often suffers from nutritional problems, both undernutrition and severe malnutrition. Nutritional needs for children need to be considered early in their lives. Malnutrition can have unavoidable bad consequences, namely the worst manifestation can cause death. It is recorded that hundreds of millions of children in the world suffer from deficiencies, meaning that this problem occurs in a very large population. Objective: To determine the factors related to the nutritional status of children at the Moanemani Health Center, Dogiyai Regency. Method:This type of research is quantitative with a Cross Sectional Study approach, the research sample was 75 children with a total sampling technique. The data were analyzed using the SPSS (Statistical Program For Social Science) version 16.0 application using the chi square test. Results: The relationship between maternal employment and p-value (0.02) <0.05, family income valuep-value(0.39) >0.05, maternal education p-value (0.21) >0.05, and maternal knowledge p-value (0.00) <0.05 on toddler nutritional status. Conclusion: Family income and pThere is no significant relationship between maternal education and child nutritional status,workMothers and mothers' knowledge have a significant relationship with the nutritional status of children at the Moanemani Health Center, Dogiyai Regency.. Suggestion: It is expected that mothers at the Moanemani Health Center can update their knowledge about nutritional status so that the nutritional status of children is also optimal.